A device for automated laser delivery in retinal photocoagulation. Issue 10 (October 1981) - Hamilton, A M; Doran, R M
Abstract : We report a modification to the argon-krypton laser (Lasertek Model AK 41) which allows optional automatic operation. This is a safe, time-saving device for use in cases requiring extensive retinal laser treatment.